Dynamic handgrip exercise for the detection of myocardial ischemia using fast Strain-ENCoded cardiovascular magnetic resonance - Ochs, Andreas; Nippes, Michael; Salatzki, Janek; Weberling, Lukas D.; Osman, Nael; Riffel, Johannes; Katus, Hugo; Friedrich, Matthias; Frey, Norbert; Ochs, Marco; André, Florian (Journal of cardiovascular magnetic resonance, 2025)
Background - Previous data suggest dynamic handgrip exercise (DHE) as a potential physiological, needle-free stressor feasible for cardiovascular magnetic resonance (CMR) examinations. DHE-fast Strain-ENCoded imaging (fSENC) is potentially cost-saving, ultra-fast and avoids pharmacological side effects thereby targeting the drawbacks of conventional pharmacological stress CMR. - Objectives - To assess the diagnostic accuracy of DHE-fSENC for detecting ischemia-related wall motion abnormalities in suspected obstructive coronary artery disease (CAD). - Methods - Patients with known or suspected obstructive CAD referred for CMR stress testing were prospectively enrolled. Diagnostic accuracy was assessed in comparison to pharmacological stress CMR and in a subgroup, compared to invasive coronary angiography (ICA). The CMR protocol was extended by both-handed DHE with 80 repetitions per minute over 2 min followed by fSENC short-axis acquisition before pharmacological stress testing. Stress-induced impairment of regional longitudinal strain was graded suspicious for obstructive CAD. - Results - Two-hundred sixty individuals with cardiovascular high-risk profile (64±13years, 75% male) were enrolled. DHE-fSENC provided a sensitivity of 79% (95% CI: 64-89) and specificity of 87% (95% CI 82-91) compared to pharmacological stress CMR. In a subgroup of 105 patients with recent ICA, high diagnostic accuracy was found for the detection of obstructive CAD (sensitivity 82% [95% CI: 67-92], specificity 89% [95% CI: 78-95]). Exam duration of DHE-fSENC was significantly reduced compared to conventional CMR stress protocols (DHE-fSENC 207±69 s vs. adenosine-perfusion 287±82 s vs. dobutamine-cine 1132±294 s, all p<0.001). - Conclusion - DHE-fSENC allows for a reliable and fast detection of obstructive CAD, thereby expanding the applicability of needle-free CMR stress testing.
Gesehen am 20.10.2025